Sistematización del proyecto de intervención socio educativo para la prevención de violencia contra la infancia. :Experiencia con los niños, niñas, padres y madres de familia de la escuela de educación básica Carlos Vicente Andrade de la comunidad Pambamarca- Cangahua, cantón Cayambe - Pilca Lanchimba, Segundo Enrique (2015)
Violence is a social phenomenon readily detectable through cultural practices family. This has led to generate aggression in family violence is in the vicinity of Community experiential level, in view of the problems students Salesian University developed the Systematization Project Socio-Educational Intervention for the Prevention of Violence against children. Experience with children, fathers and mothers School of Basic Education Carlos Vicente Andrade of Pambamarca-Cangahua Community, Canton Cayambe. The method was applied during the process was descriptive and explanatory, had a thoughtful approach in order to raise awareness among parents and children about situations of violence, its causes and consequences. For advocacy work, using techniques of group work, discussions among stakeholders prioritized. These techniques allowed not only analyzing the problem of violence and its impact at the level of family and social spheres but also making commitments and strategies to overcome violent practices.